Who Makes It to the Top? Differential Rewards to Personality across Gender and Occupation in the UK - Cecily Josten; Grace Lordan (Institute of Labor Economics (IZA), 2024)
This study tests whether personality traits are legitimately rewarded in the labour market or whether there are differing rewards across gender that cannot be explained with productivity. We investigate if personality traits affect the likelihood of making it to the top income quintile within an occupation differently by gender using UK Household Longitudinal data. We find that being agreeable hurts men more than women across a majority of occupations, which points at the role of gender norms for wages. Further, female legislators and senior officials who are conscientious, extraverted, neurotic and open are more likely to be among the top earners than men. Other than that, we find small gender differences in personality rewards.
Keywords: J16; J24; J31; 330; personality traits; agreeableness; Big Five; labor market; earnings; gender wage gap